La "Nueva Gramática de la lengua Castellana" de Martínez de Noboa.: La coherencia interna de una doctrina - Maquieira Rodríguez, Marina A.; Koerner, E. F. K., 1939-; Niederehe, Hans-Josef, 1937- (Amsterdam/ Philadelphia: John Benjamins Publishing Company, 2001)
This paper examines a treatise on Spanish grammar, i.e., a particular grammar which follows the tradition of French philosophical grammar. Bachiller D. Antonio Martinez de Noboa's work, published in 1839, appears in a century when the Spanish grammatical tradition is at its best. Texts like Vicente Salvó's (1786-1849) and of course Andres Bello's (1781-1865) have in recent years attracted the attention of researchers. However, Martinez de Noboa's work is much less known, although Gomez Asencio (1981, 1985) did highlight its importance in his two indispensable studies of the period between 1771 and 1847. The Nueva Gramótica de la lengua Castellana is indebted to the framework set by José Gomez de Hermosilla (1835) and Jacobo Saqueniza (1828), although it does include some original observations. This paper examines the structure of the work in question and aims to show how it is in global terms a unified text combining different aspects, of which the most striking is without doubt the syntactic one. With this aim in mind certain specific examples of the analogy pertaining to syntax have been studied. First those he himself highlighted, e.g., the article/pronoun and verb and then those comments on syntax which are logically pertinent, e.g., conjunctions. Noboa himself was cited as was Saqueniza as having been responsible for the introduction of distinction between coordinate and subordinate conjunctions in Spanish grammar, along with the distinction between simple and complex clauses. On the purely syntactic level, it was also Noboa who refined the whole notion of verbal government. Finally, there is a brief summary of the section dedicated to pronunciation and spelling which are also considered by the author to be in some way related to the other parts of the grammar. In sum, what makes this work particularly interesting is undoubtedly the emphasis on syntax as more studies had been carried out on morphology than in any other area up until the 19th century and continued after Noboa to monopolise questions concerning grammar throughout this century.
Keywords: Martínez de Noboa, Antonio; Gramática; Lengua española